Whole-Genome Sequencing of Invasion-Resistant Cells Identifies Laminin α2 as a Host Factor for Bacterial Invasion - Xander M. van Wijk; Simon Döhrmann; Björn M. Hallström; Shangzhong Li; Bjørn G. Voldborg; Brandon X. Meng; Karen K. McKee; Toin H. van Kuppevelt; Peter D. Yurchenco; Bernhard O. Palsson; Nathan E. Lewis; Victor Nizet; et al. (mBio, 2017)
ABSTRACT To understand the role of glycosaminoglycans in bacterial cellular invasion, xylosyltransferase-deficient mutants of Chinese hamster ovary (CHO) cells were created using clustered regularly interspaced short palindromic repeat (CRISPR) and CRISPR-associated gene 9 (CRISPR-cas9) gene targeting. When these mutants were compared to the pgsA745 cell line, a CHO xylosyltransferase mutant generated previously using chemical mutagenesis, an unexpected result was obtained. Bacterial invasion of pgsA745 cells by group B Streptococcus (GBS), group A Streptococcus, and Staphylococcus aureus was markedly reduced compared to the invasion of wild-type cells, but newly generated CRISPR-cas9 mutants were only resistant to GBS. Invasion of pgsA745 cells was not restored by transfection with xylosyltransferase, suggesting that an additional mutation conferring panresistance to multiple bacteria was present in pgsA745 cells. Whole-genome sequencing and transcriptome sequencing (RNA-Seq) uncovered a deletion in the gene encoding the laminin subunit α2 (Lama2) that eliminated much of domain L4a. Silencing of the long Lama2 isoform in wild-type cells strongly reduced bacterial invasion, whereas transfection with human LAMA2 cDNA significantly enhanced invasion in pgsA745 cells. The addition of exogenous laminin-α2β1γ1/laminin-α2β2γ1 strongly increased bacterial invasion in CHO cells, as well as in human alveolar basal epithelial and human brain microvascular endothelial cells. Thus, the L4a domain in laminin α2 is important for cellular invasion by a number of bacterial pathogens. IMPORTANCE Pathogenic bacteria penetrate host cellular barriers by attachment to extracellular matrix molecules, such as proteoglycans, laminins, and collagens, leading to invasion of epithelial and endothelial cells. Here, we show that cellular invasion by the human pathogens group B Streptococcus, group A Streptococcus, and Staphylococcus aureus depends on a specific domain of the laminin α2 subunit. This finding may provide new leads for the molecular pathogenesis of these bacteria and the development of novel antimicrobial drugs.